IMPLEMENTASI PROGRAM TRADE SUPPORT PROGRAM (TSP) DALAM HUBUNGAN KERJASAMA PERDAGANGAN INDONESIA DAN UNI EROPA TAHUN 2010-2014 - Niki Yuliana; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe the implementations of trade support program in trade cooperations between Indonesia European Union in 2010-2014. Nowdayas Europan Union are one of regions that have big potencial market for Indonesia. But since have a cooperation with European Union, eport product from Indonesia always get a protection from Europan Union. In order that government of Indonesia has implemented a trade supprot program to increase a quality and quantity of export product from Indonesia.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the implementations of trade support program in trade cooperations between Indonesia European Union. The theories applied in this research are liberalism perspective with international cooperation theory.The conclusion of the research about the implementations of trade support program in trade cooperations between Indonesia European Union are have done because protection policy of European Union toward export product from Indonesia. Some trade protection Europan Union are weakness of standarization of product, weakness of competitiveness product from another state, instability of politic and security dosemstic, the high of quality standart from European Union and the policy of tariff and trade from Europan Union.Key words: implementation, trade, support and program